Operative risk stratification in the obese female undergoing implant‐based breast reconstruction. Issue 6 (1st July 2019) - Rudolph, Megan; Moore, Catherine; Pestana, Ivo A.
Abstract: The prevalence of obesity is growing, and breast reconstruction in the obese patient is becoming the norm rather than the exception. Our aim was to evaluate implant reconstruction outcomes in the obese female in the presence of coincident surgical risk factors and identify potential risk‐reducing interventions. A review of consecutive obese women (BMI ≥ 30) who underwent mastectomy and implant breast reconstruction was performed. Patient demographics, comorbidities, oncologic treatments, and reconstructive procedures and their complications were recorded. A total of 151 women (242 breast reconstructions) were included with mean follow‐up of 28 months. Average BMI was 36. Eighty percent of cases were immediate and 20% delayed. ADMs were utilized in 58% of cases. About 25% of patients had diabetes with one‐third achieving perioperative glycemic control. About 18% of women were active smokers, and 33% had radiotherapy. Major and minor complications occurred in 42% and 11% of patients, respectively. About 24% of reconstructed breasts required implant removal. Obese patients with prior radiation were three times as likely to develop infection ( P  = 0.008) and 2.5× as likely to undergo explantation ( P  = 0.002). Skin flap necrosis was three times as likely in obese smokers ( P  = 0.01). Increased rates of wound breakdown were identified in obese patients with increasing age ( P  = 0.005), smoking ( P  = 0.0035), and radiation ( P  = 0.023). In the obese radiated and smoking patient subgroups, surgical modifications (use of autologous tissue, delayed breast reconstruction timing, and no ADM) were associated with reduction in the relative risk for implant complications. While obesity alone increases implant breast reconstruction complication rates, the presence of additional risk factors compounds these rates. The use of surgical modifications may reduce the occurrence of perioperative complications in the obese female with coincident surgical risk factors undergoing implant breast reconstruction.